Differences between traditional and modern technology in the acquisition of new ski knowledge - Marinovic, M.; Kuna, D.; Macan, I. (Studia Sportiva, 2022)
Purpose: Video materials have been used as teaching tools for many years. With the development of modern technology, new video devices have appeared that have greatly improved the quality and capabilities of video materials. This study was conducted with the purpose of investigating and comparing the current traditional and modern ways of recording ski elements. In the traditional way of recording, the cameraman stands on the ski slope and uses a camera to record a demonstration of the ski element of the skier moving toward him. On the other hand, the modern way of recording was made with the Gopro 360 max, which allows you to record video while skiing.